1997
DOI: 10.1046/j.1365-2141.1997.8532481.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood viscosity and risk of cardiovascular events: the Edinburgh Artery Study

Abstract: Summary.We examined the relationships of whole blood viscosity and its major determinants to incident cardiovascular events (ischaemic heart disease and stroke) in a prospective study of a random population sample of 1592 men and women aged 55-74 years (the Edinburgh Artery Study). 272 fatal and non-fatal cardiovascular events occurred during 5 years of follow-up (cumulative incidence 17 . 1%). Age and sex adjusted mean levels of blood viscosity (3 . 70 v 3 . 55 mPa.s), haematocrit (46 . 2 v 45 . 7%), haematoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
332
1
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(353 citation statements)
references
References 25 publications
9
332
1
11
Order By: Relevance
“…In contrast, the subset of SLE patients with arterial thrombotic events did have significantly elevated WBV. This is in concordance with population studies, which suggest that high blood viscosity is associated with arterial events such as cardiovascular and cerebrovascular disease (11)(12)(13). It is possible that WBV is a nontraditional risk factor linked to atherothrombotic disease in SLE.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the subset of SLE patients with arterial thrombotic events did have significantly elevated WBV. This is in concordance with population studies, which suggest that high blood viscosity is associated with arterial events such as cardiovascular and cerebrovascular disease (11)(12)(13). It is possible that WBV is a nontraditional risk factor linked to atherothrombotic disease in SLE.…”
Section: Discussionsupporting
confidence: 89%
“…Because multiple traditional cardiovascular risk factors such as age, male sex, obesity, hypertension, diabetes, and smoking are all associated with increased viscosity, the correlation between viscosity and atherothrombotic events decreases after adjustment for these risk factors (9,14). However, there may be an additional, independent increase in risk for such events associated with high blood viscosity itself (12,13,15).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-five percent (55%) of major cardiovascular events occurred in the highest blood-viscosity group versus only 4% in the lowest blood-viscosity group. 39 The role of increased blood viscosity in the pathogenesis of occlusive arterial disease was clearly and succinctly described by Kensey. 15 Endothelial dysfunction, mechanical shear forces, and alterations in blood flow mechanics at arterial bifurcations and areas of low blood flow eddies are correlated with plaque progression in the coronary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also recently reported from the Edinburgh Artery Study cohort of men and women aged 55 to 74 years. 8 To date, several prospective studies have convincingly documented an association between fibrinogen and CHD. 5 In some of these analyses, an association with stroke (Gothenburg Study, Framingham Study 8 ) was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma viscosity, as well as fibrinogen and white blood cell count, was positively associated with the incidence of CHD events in a population-based study of middle-aged men. 6,7 Plasma viscosity and fibrinogen were also associated with incident CHD and stroke in a study of older men and women 8 and with recurrence of stroke in another study. 9 In the first cross-sectional study of the MONICA Project, Augsburg, 1984 to 1985, plasma viscosity but not fibrinogen was measured in addition to conventional risk factors.…”
mentioning
confidence: 97%